Do peer-support groups for voice-hearers work? A small scale study of Hearing Voices Network support groups in Australia. Issue 1 (2nd January 2017) - Beavan, Vanessa; de Jager, Adele; dos Santos, Bianca
Abstract: Hearing Voices Network (HVN) support groups have proliferated in the last decade, with anecdotal evidence suggesting they contribute significantly to the recovery trajectory of the voice-hearer members who attend them. However, to date there remains little empirical research into the efficacy of these groups and the processes that might underpin their efficacy. This article describes a small project evaluating the HVN groups in the large Australian state of New South Wales. Twenty-nine group members completed questionnaires exploring self-reported recovery-related and clinical outcomes, aspects of group process, and the extent to which core HVN principles were promoted within the group. Results indicate that HVN groups are associated with reported improvements across a number of recovery-related outcomes including feeling less isolated and more skilled in being with others, having improved self-esteem, and having a better understanding of their voice experiences. Positive changes were also noted in outcomes that are more traditionally associated with clinical improvements, such as decreased need for emergency help and medication, and increased hope in personal recovery. Although this study is small and based on self-report, the findings are promising and contribute to the small but growing literature on peer-supported interventions for psychosis and psychotic-like experiences.